ANALISIS KESADARAN POLITIK MASYARAKAT DESA MARIORILAU KECAMATAN MARIORIWAWO TERHADAP TINGKAT PARTISIPASI DALAM PEMILIHAN BUPATI KABUPATEN SOPPENG - Gustina Gustina; Dr. Mustaring; Nurharsyah Khaer (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2019)
Abstract; This study aims to determine: Community Participation Level Mariorilau Village, Kec. Marioriwawo in the District Regent Election. Soppeng, Factors influencing public participation in the Election of Regent of Soppeng Regency, and Efforts made by the General Election Commission in increasing public participation in the Election of Regent of Soppeng. To achieve these objectives the researchers used qualitative methods with descriptive research types. The population in this study was 4.037 people and a sample of 100 people, the sampling technique used was proportional random sampling. Data collection techniques using questionnaires (questionnaires), interviews, and documentation. Meanwhile, the data analysis technique used in this study to analyze the data from the interviews and documentation used descriptive analysis, while the data from the questionnaire results will be processed by the percentage analysis technique in the form of frequency. From the results of the study, it can be concluded that: First, the level of community participation in the election of the Regent of Soppeng Regency by voting was 89% (high community participation rate). Second, the factors that support the community in participating are the political awareness of the community and the level of education of the community itself, while the inhibiting factors are the busyness of daily activities and the indifferent attitude of the community. Third, as well as the efforts made by the Soppeng Regency General Election Commission to increase public participation in the election of the Soppeng Regent in the form of socialization, and programs namely, socialization with religious segments, outreach from house to house, socialization of market raids and discussions of political education.Keywords: Awareness, politics, participation